2022
DOI: 10.1021/acs.chemrestox.2c00129
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, Pharmacology, and Toxicology of Monoisoamyl Dimercaptosuccinic Acid: A Chelating Agent for Chronic Metal Poisoning

Abstract: Arsenic, a metalloid, is known to cause deleterious effects in various body organs, particularly the liver, urinary bladder, and brain, and these effects are primarily mediated through oxidative stress. Chelation therapy has been considered one of the promising medical treatments for arsenic poisoning. Meso 2,3- dimercaptosuccinic acid (DMSA) has been recognized as one of the most effective chelating drugs to treat arsenic poisoning. However, the drug is compromised with a number of shortcomings, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…While orally- or intravenously-administered chelating agents can be an effective strategy to treat As III , Cd 2+ , Hg 2+ and Pb 2+ exposed individuals [ 128 ], adverse effects of chelation therapy frequently occur [ 129 ]. Thus, more effective chelating agents that offer fewer side effects continue to be developed [ 130 , 131 ]. Recent results, which involved N-acetyl-L-cysteine (NAC), provided important new insight into the mobilization of CH 3 Hg + from tissues.…”
Section: Advances Into the Toxicological Chemistry Of CD 2+...mentioning
confidence: 99%
“…While orally- or intravenously-administered chelating agents can be an effective strategy to treat As III , Cd 2+ , Hg 2+ and Pb 2+ exposed individuals [ 128 ], adverse effects of chelation therapy frequently occur [ 129 ]. Thus, more effective chelating agents that offer fewer side effects continue to be developed [ 130 , 131 ]. Recent results, which involved N-acetyl-L-cysteine (NAC), provided important new insight into the mobilization of CH 3 Hg + from tissues.…”
Section: Advances Into the Toxicological Chemistry Of CD 2+...mentioning
confidence: 99%
“…It has been used since the 1950s. It is a lipophilic chelator and, therefore, is also a chelating agent for other divalent metals such as mercury, arsenic, cadmium, and gallium arsenide [ 43 ]. It is an organic sulphur compound with two sulfhydryl groups with the formula C 4 H 6 O 4 S 2 .…”
Section: Antidotes For Metal Intoxicationsmentioning
confidence: 99%
“…19 Although many studies have confirmed heavy-metal-induced oxidative stress, the usefulness of antioxidants along with chelation therapy has not been extensively investigated. 20 Traditionally, medicinal plants have always been used as the primary constituent for the remedy of various illnesses. Recently, India and countries around the globe have used alternative medicines and medicinal herbs, and their bioactive compounds are familiar because they cure various kinds of illnesses by synchronizing with the body's immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have confirmed heavy-metal-induced oxidative stress, the usefulness of antioxidants along with chelation therapy has not been extensively investigated. 20 …”
Section: Introductionmentioning
confidence: 99%